Graft copolymer films and nanoporous polypropylene membranes with polypropylene backbone

The preparation of nanoporous membranes by using random graft copolymers with PP framework and 3-8 polyester grafts has solved the problems of existing membranes at low operating temperatures, inability to sterilize, limited flux and susceptibility to contamination at low operating temperatures, limited operation, and susceptibility to contamination. , nanoporous membranes with high throughput and good mechanical properties have been achieved, expanding their application range.

CN113677423BActive Publication Date: 2025-02-25SABIC GLOBAL TECHNOLOGIES BV
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202080025476.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-03-29
Filing Date
2020-03-12
Publication Date
2025-02-25
Estimated Expiration
2040-03-12

AI Technical Summary

Technical Problem

The existing nanoporous membranes have defects in low operating temperature, inability to sterilize, limited flux and susceptibility to contamination, which limits its application scope.

Method used

Nanoporous membranes are prepared using random graft copolymers with polypropylene (PP) framework and 3-8 polyester grafts. By adjusting the composition and structure of PP and polyester, a bicontinuous phase is formed to improve the mechanical properties of the membrane. and flux.

Benefits of technology

The nanoporous membrane used at high temperatures is achieved, with high throughput and good mechanical properties, and the size of the nanopores can be adjusted by selecting a combination of PP and polyester, which expands the design freedom and application range of the membrane.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003283861730000161
    Figure BDA0003283861730000161
  • Figure BDA0003283861730000181
    Figure BDA0003283861730000181
  • Figure BDA0003283861730000191
    Figure BDA0003283861730000191
Patent Text Reader

Abstract

The present invention relates to a film comprising a random graft copolymer having a polypropylene (PP) backbone and 3-8 polyester segments covalently bonded to the backbone, wherein the number average molecular weight (Mn) of the polypropylene backbone is 10.000-100.000 Daltons (determined by HT-SEC in o-DCB at 150°C), wherein the Mn of each polyester segment is 5.000-25.000 Daltons, wherein the amount of PP is 45-80 mol%, wherein the amount of polyester segments is 55-20 mol%, wherein the thickness of the film is 0.01-10 mm, wherein the regions of the polypropylene and the polyester independently form a continuous phase, and wherein the mol% is calculated relative to the total moles of the monomer units present in the copolymer. The present invention also relates to a nanoporous PP film and its application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a film comprising a graft copolymer having a polypropylene (PP) backbone and polyester grafts attached to the backbone, a nanoporous PP membrane obtained from the film and the use thereof. Background Art

[0002] Thin films comprising polyolefins coupled to polyesters are known in the art. Additionally, nanoporous membranes of polyolefins are also known in the art.

[0003] Membrane technology is becoming increasingly important as a widely used separation technology. Water purification and industrial separation processes are good examples. Non-porous reverse osmosis membranes (i.e. water desalination, gas separation) and porous microfiltration / ultrafiltration / nanofiltration membranes are used. Polyvinylidene fluoride, poly(ethylene-co-chlorotrifluoro-ethylene), polysulfone, polyethersulfone, polyphenylsulfone and aromatic polyamide are the most commonly used materials for membrane production [1]. Although these special polymers have excellent mechanical properties, the average raw material price of $10-$20 / kg is very expensive. In addition, the recycling or incineration of polyvinylidene fluoride or polysulfone, etc., also poses risks in terms of pollution and release of toxic components.

[0004] Currently, most membranes used for microfiltration, ultrafiltration and nanofiltration are diaphragmatically controlled by opening (e.g. microporous membranes [2]), track etching (e.g. NucleporeTM,[3]), template leaching[4] or phase separation method using block copolymers[5],[6].

[0005] Cracking is the initial fracture process that leads to the development of certain fracture morphologies. Cracking occurs when excessive tensile stress is applied to a polymer, resulting in the formation of microvoids in the plane perpendicular to the stress.

[0006] As precursor materials in membrane technology, block copolymers have attracted increasing attention due to their ability to form membranes with the following properties: tunable pore size and narrow pore size distribution, high flux, high selectivity, the ability to be selectively functionalized, and good mechanical properties. The two main strategies for forming pores in block copolymer membranes are (1) self-assembly and phase separation as described above, and (2) membrane calendering and selective block sacrificialization [5], [6].

[0007] Polyolefin-based nanoporous membranes.

[0008] Phase separation methods that require solvent casting, such as SNIPS, are not applicable to most polyolefin-based block copolymers due to the poor solubility of polyolefins in environmentally friendly solvents [5]. Track etching is a relatively expensive technique for producing nanoporous polycarbonate and polyethylene terephthalate membranes [3] and is also rarely applicable to polyolefins. Most commonly, polyolefin-derived microporous and nanoporous (>100 nm) membranes are produced by controlled cracking [2]. Although this preparation technology is mature, the relatively large pore size and uneven pore size distribution of the membrane limit its application. Alternatively, template leaching methods have been developed, in which mixtures of polyolefins and solvents, oils or other polymers are allowed to undergo thermally induced phase separation (TIPS), followed by removal of the solvent, oil or polymer by extraction to produce polyolefin-based microporous membranes [4].

[0009] Selective fragment sacrificial process

[0010] A similar strategy was applied to produce nanoporous membranes starting from amphiphilic block copolymers. The phase separation-induced morphology of such block copolymers can be nudged by varying the volume fraction of each component forming the block copolymer. When a cylindrical or helical bicontinuous morphology (also called a bicontinuous phase) is formed, the degradable segments (such as polyester, polybutadiene or polysiloxane) can be selectively removed by etching, leaving behind a nanoporous polymer material. This selective segment sacrificial technique was first reported for the production of polystyrene-based nanoporous membranes [6], but has recently been applied to the production of polyethylene-based nanoporous membranes as well [7]. Hillmyer and co-workers prepared PE-based block copolymers by catalytic ring-opening polymerization starting from hydroxyl-functionalized hydrogenated polybutadiene as a macroinitiator to produce the corresponding PE-PLA block copolymers [7b-c]. The bottleneck of this approach is the cumbersome and expensive three-step synthetic process for the production of OH-functionalized PE, which includes a ring-opening metathesis polymerization (ROMP) of cyclooctene, followed by air oxidation and a final hydrogenation step. In addition, it is limited to the production of PE-based films, which limits thermal stability and, for example, cannot be sterilized. Coordination chain transfer polymerization followed by in situ air oxidation offers a relatively simple and inexpensive synthetic method for obtaining chain-end functionalized polyolefins [7a,e]. However, this method must be carried out in solution at elevated temperatures, otherwise only low molecular weight (<5 kDa) products are obtained, since the chain process becomes ineffective once the polymer starts to crystallize from solution. In addition, the effectiveness of the post-polymerization functionalization step is limited to 80%. Therefore, the formation of chain-end functionalized polyolefin macroinitiators corresponding to block copolymer precursors is limited to PE-based products produced in a three-step process or products with a maximum functionality of 80% in a two-step process.

[0011] WO2011112897A1 describes a block copolymer precursor for a nanoporous linear polyolefin membrane and its application. The patent application mentions that the polyolefin can be polyethylene (PE) or PP, but only gives linear PE as an example of a polyolefin block. The linear PE block is derived from a terminated hydrogenated polybutadiene polymer chain, which is subsequently copolymerized with a cyclic ester to prepare a polyester-polyolefin-polyester copolymer. The patent application does not explain how to prepare a triblock copolymer from PP, which cannot be derived from polybutadiene.

[0012] The problems of PE-based nanoporous membranes are low operating temperature, inability to sterilize, limited flux of the membrane and susceptibility to membrane contamination, thus limiting the flow rate of the nanoporous membrane.

[0013] To date, there are no reports of semi-crystalline membranes that are not based on PE polyolefins. One of the main drawbacks of PE or random polyethylene-cyclohexane based membranes is that their melting point and glass transition point (T g ) are too low to be sterilized[9]. By replacing them with high melting point polyolefins such as isotactic or syndiotactic polypropylene, poly(4-methyl-1-pentene), polyethylene-cyclohexane, and poly(3-methyl-1-butene), a retortable film can be obtained.

[0014] The use of polyolefin-based graft copolymers for the production of nanoporous membranes has several advantages: the production of randomly functionalized polyolefin macroinitiators is a one-step process and functionalized polyolefins with a wide range of chemical structures, melting points and molecular weights can be produced.

[0015] Typically, PE-polyester block copolymers are produced by ring-opening polymerization of lactones using PE functionalized with hydroxyl chain ends. Although this is an effective method on a laboratory scale, the method requires dissolved PE macroinitiators, which is difficult and costly to scale up.

[0016] It is an object of the present invention to overcome at least some of these and other disadvantages. Summary of the invention

[0017] The present invention relates to a film comprising:

[0018] - random graft copolymers having, when all functional groups have reacted, a polypropylene (PP) backbone and up to 3 to 8 polyester segments covalently bonded to said backbone (also called grafts),

[0019] - wherein the number average molecular weight M of the PP skeleton n (measured by HT-SEC in o-DCB at 150° C.) of 10-100 kDa, preferably 20-100 kDa,

[0020] - wherein each polyester segment has an M n5-25 kDa (at 90 °C in tetrachloroethane-d2 1 H NMR measurement),

[0021] - The amount of PP in the skeleton is 45-80 mol%.

[0022] - wherein the amount of polyester in the polyester segment is 55-20 mol%,

[0023] - wherein the thickness of the film is 0.01-10 mm,

[0024] - where the regions of PP and polyester form a co-continuous phase,

[0025] - wherein the mol % is calculated relative to the total number of moles of monomer units propylene and ester present in the copolymer.

[0026] The present invention also relates to a nanoporous membrane comprising at least 90 wt% PP, wherein the PP has 3-8 OX groups per polymer chain, wherein the membrane has pores of size 20-50 nm (measured by N2-adsorption according to the Barret-Joyner-Halenda model) and a surface area of ​​50-200 m 2 / g, wherein for each –OX, X is selected from H, Li, Na and K.

[0027] The membrane of the invention can be used at high temperatures, making it possible to sterilize the membrane. Surprisingly, the membrane has a high flux of aqueous media, so that its flux is very high. In addition, it has been found that by choosing the right combination of PP and polyester, the size of the nanopores can be adjusted, which enlarges the design freedom and the range of use of the membrane.

[0028] It has been found that the type of polyester used as sacrificial segment in the corresponding graft copolymer has a significant effect on the pore size. For example, changing polyvalerolactone to polycaprolactone, while maintaining the same mole fraction, results in a 50% reduction in pore size.

[0029] The bicontinuous phase or bicontinuous helical morphology is a known crystalline phase that lies between the lamellar and columnar phases for polymers.

[0030] In other words, the following feature: when all functional groups are reacted, a random graft copolymer having a PP backbone and up to 3-8 polyester grafts covalently bonded to the backbone (wherein the regions of PP and polyester form a bicontinuous phase) can also be described as "a random graft copolymer having a PP backbone and 3-8 polyester grafts, wherein the graft copolymer exists in the form of a nanostructured bicontinuous spiral, which contains two interpenetrating continuous phases, one continuous phase containing the PP portion of the graft copolymer, and the other continuous phase containing the polyester portion of the graft copolymer."

[0031] However, it is possible that not all functional groups react, so the number of polyester grafts can be 1-8.

[0032] Compared to the triblock copolymers described in prior art WO 2011 / 112897, such multi-graft copolymers can have more than two functional groups per chain. The presence of the graft segments allows for higher reactivity due to sterically unhindered side chain OH groups instead of OH groups at the PP chain ends. DETAILED DESCRIPTION

[0033] The present invention relates to a film comprising:

[0034] - a random graft copolymer having a polypropylene (PP) backbone and 3 to 8 polyester grafts (also called segments) covalently bonded to said backbone,

[0035] - wherein the number average molecular weight (M n ) is 10-100 kDa (measured by HT-SEC in o-DCB at 150° C.), preferably 20-100 kDa,

[0036] - wherein each polyester segment has an M n 5-25 kDa (at 90 °C in tetrachloroethane-d2 1 H NMR measurement),

[0037] - The amount of PP in the skeleton is 45-80 mol%.

[0038] - wherein the amount of polyester in the polyester segment is 55-20 mol%,

[0039] - wherein the thickness of the film is 0.01-10 mm,

[0040] - wherein the domains of PP and polyester form a co-continuous phase,

[0041] - wherein the mol % is calculated relative to the total number of moles of monomer units propylene and ester present in the copolymer.

[0042] SEC-DV stands for Size Exclusion Chromatography - Differential Viscometer. The measurements are carried out in o-dichlorobenzene (o-DCB). The SEC instrument is equipped with an infrared detector and an online viscometer. The Mark-Houwink plot gives the size (viscosity) as a function of molar mass and is generally linear for samples without long chain branches (LCB), but shifted if LCB is present.

[0043] Mn (in kDa) was determined using standard high temperature size exclusion chromatography (HT-SEC) as follows:

[0044] The polymer Char was prepared at 150 °C in an Agilent GC oven model 7890 equipped with an autosampler and an integrated detector IR4. The measurement was performed on a 1,2-dichlorobenzene (o-DCB) at a flow rate of 1 mL / min as the eluent. Calculations Software GPC Process the data. Calculate molecular weight based on polystyrene standards.

[0045] The film comprises a random graft copolymer having a PP backbone and polyester side chains covalently coupled to the backbone.

[0046] The PP backbone contains functional groups and is preferably prepared from a PP homopolymer or a copolymer of propylene and ethylene, wherein the amount of ethylene is less than 5 wt%.

[0047] The hydroxyl-functionalized PP in the copolymer backbone preferably has a melting temperature of at least 120° C., preferably at least 130° C., more preferably at least 135° C. or 140-160° C. The PP is preferably isotactic or syndiotactic, most preferably isotactic. This high melting point allows the film of the present invention to be sterilized, especially steam sterilized at about 120° C., without losing its mechanical properties.

[0048] The film has good mechanical properties. The Young's modulus is usually 300-1500 MPa, preferably 350-1200 MPa or 400-1000 MPa. The toughness of the film is usually 1-150 J / m 3 , preferably 2-120 J / m 3 , more preferably 4-100 J / m 3 .

[0049] PP is coupled to the polyester segment via an ester bond, whereby the original PP contains OH groups. The OH groups are preferably part of short side chains of the PP backbone. The short side chains are preferably obtained by copolymerization of propylene with an α-olefin having OH groups. The OH groups are preferably randomly distributed along the PP polymer chain. Copolymers with randomly distributed OH groups are known in the art.

[0050] WO2017097570A1 and WO2017097571A1 disclose ethylene copolymers containing OH groups in the side chains.

[0051] EP1186619 (Mitsui Chemicals Inc.) discloses olefin copolymers having polar groups.

[0052] WO2016097203 describes many examples of PP polymers with OH side chains, wherein the OH groups are coupled to polycaprolactone.

[0053] The number of OX groups (preferably the number of OH groups present in the PP (before preparation of the graft copolymer)) is 3-8 OH groups per molecule (on average). This can be determined by 1 H NMR measurements.

[0054] The molecular weight of the PP backbone is preferably 10-100 kDa (measured by HT-SEC in o-DCB at 150°C), more preferably 20-100 kDa.

[0055] When all OX groups have reacted, the graft copolymer contains 3-8 polyester chains per molecule, which are coupled to the OX groups of the original PP, which is formed by 1 HNMR tetrachloroethane-d2 measurement.

[0056] Therefore, due to the presence of a large number of OX groups in PP, it allows the production of multi-graft copolymers containing 4-9 segments (1 PP segment and 3-8 polyester segments) when all OX groups are reacted.

[0057] However, it is possible that not all functional groups react, so the number of polyester grafts may be 1-8 polyester chains per molecule.

[0058] The coupling to produce the PP-graft-polyester copolymer can be achieved by transesterification of at least one second polymer (e.g. polyester) comprising at least one carboxylate or carbonate functional group and / or by ring-opening polymerization (ROP) of cyclic esters, examples of which are caprolactone, valerolactone, p-propiolactone, p-butyrolactone, 3-methyloxetane-2-one, ε-decanolide, 5,5-dimethyl-dihydrofuran-2-one, 1,4-dioxepan-5-one, 1,5-dioxepan-2-one, 3,6-dimethylmorpholine-2,5-dione, 1,4-dioxepan-7-one, 4-methyl-1,4-dioxepan-7-one, (S)-g-hydroxy Methyl-g-butyrolactone, g-octanoic acid lactone, g-nonanoic acid lactone, 5-valerolactone, 5-hexanoic acid lactone, 5-decanoic acid lactone, 5-undecalactone, 5-dodecalactone, glycolide, lactide (L, D, meso), enantholactone, octanoic acid lactone, nonalactone, decanoic acid lactone, 11-undecalactone, 12-dodecalactone, 13-tridecalactone, 14-tetradecanoic acid lactone, 15-pentadecalactone (or pentadecalactone), pentadecenolactone, 16-hexadecanoic acid lactone, hibiscus lactone, 17-heptadecalactone, 18-octadecanoic acid lactone, 19-nonadecalactone, ethylene butylene ester, butyl butylene ester, cyclic terephthalate, cyclic butyl adipate, cyclic butyl succinate, cyclic butyl terephthalate oligomers.

[0059] The cyclic esters, particularly when they are lactones, may be in any isomeric form and may further contain organic substituents on the ring which do not prevent ROP.

[0060] Examples of such cyclic esters include 4-methylcaprolactone, ε-decanoic acid, the lactone of ricinoleic acid or its hydrogenated form, 13-hexyloxycyclotridecan-2-one, and the like.

[0061] It is also possible that the cyclic ester contains one or more unsaturations in the ring. Examples of such cyclic esters include 5-tetradecene-14-lactone, 11-pentadecen-15-lactone, 12-pentadecen-15-lactone (also known as pentadecenolactone), 7-hexadecene-16-lactone (also known as hibiscus lactone) and 9-hexadecene-16-lactone.

[0062] Cyclic esters may also have one or more heteroatoms in the ring, provided that the heteroatoms do not prevent ROP. Examples of such cyclic esters include 1,4-dioxepan-5-one, 1,5-dioxepan-2-one, 3,6-dimethylmorpholine-2,5-dione, 1,4-oxepan-7-one, 4-methyl-1,4-oxepan-7-one, 10-oxahexadecenolactone, 11-oxahexadecenolactone, 12-oxahexadecenolactone, 12-oxahexadecen-16-olactone.

[0063] The cyclic ester is preferably selected from caprolactone and valerolactone.

[0064] The polarity of the polyester segment can be adjusted, for example, by adding a combination of multiple cyclic monomers of different polarities, adjusting the polarity of the second polymer segment during presynthesis using a combination of monomers before attaching the second polymer segment to the polyolefin segment by nucleophilic substitution, adding a combination of multiple second polymers of different polarities, or adding a combination of cyclic monomers and second polymers by nucleophilic substitution. The melting temperature and / or glass transition temperature of the resulting graft copolymer graft can also be adjusted by selecting appropriate monomers for the second segment while maintaining the crystalline properties. In other words, the application of the present invention allows the adjustment of physical and mechanical properties. In addition, the hydrolysis and degradation properties of the polar polymer segment can be adjusted without affecting the polyolefin segment.

[0065] Each polyester segment M n 5-25 kDa (at 90 °C in tetrachloroethane-d2 1 HNMR measurement).

[0066] The polyester segments (such as polycaprolactone or polyvalerolactone segments) are incompatible with the linear PP backbone. This incompatibility causes the graft copolymer to phase separate at some point after synthesis from the initial homogeneous state and produce a multiphase composition with a nanostructured bicontinuous microstructure, one of which contains the polyester segments.

[0067] Depending on the composition of the PP / polyester, the copolymer forms a co-continuous phase, which means that the PP forms a continuous phase and the polyester also forms a continuous phase. The presence of a co-continuous phase can be observed using different techniques, such as transmission electron spectroscopy (TEM), scanning electron microscopy (SEM), atomic force microscopy (AFM) and / or small angle X-ray scattering (SAXS).

[0068] Within the film limits of the present invention, the amount of polyester is from about 5 to about 90 mol % (mol % calculated relative to the amount of molar units present in the copolymer).

[0069] However, in order for the film to be used as a porous membrane of the present invention, the amount of PP is 45-80 mol%, and the amount of the polyester segment is also 55-20 mol%. The amount of PP is preferably 50-75 mol%, and the amount of the polyester segment is 50-25 mol% (mol% calculated relative to the amount of molar units present in the copolymer). If this amount is not reached, the film becomes a barrier because there are no passages in the film and cannot be used as a porous membrane.

[0070] Fig.12a a, b, c, d, e, and f describe the organization and morphology of the graft copolymers depending on the number average molecular weights of polyester and polypropylene.

[0071] Fig.12a is a comparative example, which is not a graft copolymer but a block copolymer, wherein the number average molecular weight of the polyester and PP segments is within the range of the present invention. It can be easily seen that when the polyester phase is removed, the self-organization and morphology of the block copolymer do not allow the formation of a nanoporous, helical bicontinuous phase.

[0072] Figure 12b , c and d describe embodiments within the scope of the present invention, wherein the number average molecular weight and content of the polyester and PP of the graft copolymer are within the scope of the present invention.

[0073] It can be easily seen that the self-organization and morphology of the graft copolymers allow the generation of channels when the sacrificial segments are removed.

[0074] Fig.12e and 12f Comparative embodiments outside the scope of the present invention are described, wherein the number average molecular weight and content of the polyester and PP of the graft copolymer are within the scope of the present invention.

[0075] Fig.12e The comparative embodiment in which the graft copolymer contains less than 20 mol% of polyester (mol% is calculated relative to the amount of molar units present in the copolymer), the self-organization and morphology of the graft copolymer after the selective segment sacrificial process is not bicontinuous, and cannot form a porous membrane.

[0076] Fig.12f The comparative embodiment in comprises polyester segments, each polyester segment having a number average molecular weight of less than 5 kDa.

[0077] The self-organization and morphology of the graft copolymer cannot form a double continuous helical morphology.

[0078] Thin films of graft copolymers can be converted into membranes with nanopores by selectively dissolving or sacrificing the polyester (the so-called segment sacrificial process) while keeping the PP phase intact.

[0079] For example, by chemical etching with an alkali or acid, the polyester fragments can be selectively removed. After removal, multiple nanometer-sized pores will be generated. The pores are very small (for example, the pore size is on the order of 1-500 nanometers, or 5-100 nanometers, preferably 10-50nm). In addition, the pores are characterized by a relatively narrow size distribution and are substantially uniformly distributed throughout the film. These properties make nanoporous films particularly suitable for applications such as separation membranes (such as battery separators). Generally, the film can be used in a variety of applications, including separation membranes (such as battery separators), membranes for water purification, fuel cell membranes, catalytic reactors, nano templates, etc. The nanoscale bicontinuous structure produced by the above process contains interpenetrating regions throughout the material. This bicontinuity allows a mechanically strong phase to support the entire structure, while another permeable region gives the material certain specific functions. A nanoporous structure is generated by removing the functional region (polyester fragment) to obtain a material with a permeable pore structure. Due to the narrow pore size distribution and the pore structure penetrating the entire membrane, this membrane material can be used as a battery separator and a separation membrane.

[0080] The present invention therefore also relates to a nanoporous membrane. The nanoporous membrane comprises at least 90 wt % PP, preferably at least 95 or at least 98 wt % PP. The PP comprises -OX functional groups randomly distributed on the polymer chains. The amount of functional groups is 3-8 (on average) per polymer chain, which is determined by 1 H NMR measurement. For each -OX, X can be H, Li, Na or K, which makes the -OX group a -OH, -OLi, -ONa or -OK group, respectively. In another embodiment, X can also be Mg, Zn and Al.

[0081] The M of PP in the film n Preferably it is 10-100 kDa, more preferably 20-100 kDa, as determined by HT-SEC (in o-DCB at 150°C). PP is preferably a propylene homopolymer, or a copolymer of ethylene and propylene, wherein the amount of ethylene is less than 5 wt%.

[0082] The PP is preferably isotactic or syndiotactic, more preferably isotactic.

[0083] The thickness of the film may be 0.01-10 mm.

[0084] The membrane preferably has pores with a pore size of 1-500 nm, preferably 5-100 nm, more preferably 10-50 nm (measured by N2-desorption according to the Barret-Joyner-Halenda model), and a BET surface area of ​​50-200 m 2 / g (measured by the Brunauer-Emmet-Teller method).

[0085] The film has preferred mechanical and thermal properties.

[0086] The film has high thermal stability and can be sterilized. The melting temperature (T m ) is 120-160°C, preferably 130-159°C, more preferably 140-158°C. m Measured by DSC (second heating curve, heating at 10 K / min).

[0087] The Young's modulus of the film is 50-400 MPa, preferably 100-300 MPa. The toughness of the film is 0.1-15 J / m 3 , preferably 0.5-10 J / m 3 .

[0088] It has surprisingly been found that after sacrificing the polyester segment, the type of polyester segment affects the microstructure of the film and thus the nanopore structure of the membrane. For example, when valerolactone is used as the polyester segment monomer, larger pores can be obtained compared to using caprolactone as the monomer.

[0089] It is believed that the presence of OX groups in the PP membrane results in a membrane with a unique structure, which has the advantage of obtaining a membrane with good mechanical properties and good flux properties. It has been found that the flux of water or aqueous solutions through the membrane is higher than other membranes with similar pore sizes. This means that at a given membrane pressure difference, a greater amount of aqueous solution flows through a membrane with a determined surface and thickness.

[0090] The invention further relates to the use of the membrane according to the invention for producing membranes which are suitable for use as water filters or battery separators.

[0091] The present invention relates to a water filter system comprising the nanoporous membrane of the present invention.

[0092] The invention also relates to a battery comprising the nanoporous membrane according to the invention.

[0093] The invention also relates to a process for the preparation of a film as defined in the invention.

[0094] The method comprises the following steps:

[0095] a) providing a hydroxy-functionalized PP having 3 to 8 hydroxyl groups,

[0096] b) preparing the graft copolymer by any of the following processes:

[0097] a. Ring-opening polymerization (ROP) of cyclic esters, or

[0098] b. Use a suitable transesterification catalyst to carry out polyester transesterification,

[0099] c) and forming a film by the following process:

[0100] a. extruding the copolymer at a temperature of at least 180°C to prepare a film having a spiral bicontinuous morphology through a film extrusion die, or

[0101] b. Film preparation by compression molding.

[0102] The present invention also relates to a PP film unit, which may be a multilayer film or a plurality of films, wherein the layers or films comprise

[0103] 1. A nanoporous membrane as defined above,

[0104] 2. Micron porous PP film and / or PP nonwoven material.

[0105] The present invention also relates to a polypropylene based film comprising the nanoporous membrane of the present invention as defined above and a microporous polypropylene film and / or a polypropylene nonwoven.

[0106] The invention also relates to the use of nanoporous membranes for the preparation of all-PP membranes for use in, for example, batteries, water filters or other applications. Some advantages of all-PP membranes are that they can be used at high temperatures, can be sterilized and can have high throughput for efficient separation of components in, for example, aqueous media. They can also be easily recycled and become part of a circular economy.

[0107] Attached photos:

[0108] Figure 1 : Isotactic poly(propylene-co-undecylenol) precursor for the synthesis of iPP-g-PVL and iPP-g-PVL copolymers 1 H NMR spectrum, in which the methylene proton signals associated with the side-chain OH groups are magnified for clarity, measured at 90 °C in tetrachloroethane-d2.

[0109] Figure 2 :iPP-g-PVL copolymer (iPP 53mol% -g-PVL 47mol% )of 1H NMR spectrum, in which the methylene proton signals associated with the side-chain OH groups are magnified for clarity, measured at 90 °C in tetrachloroethane-d2.

[0110] Figure 3 :iPP-g-PCL copolymer (iPP 53mol% -g-PCL 47mol%) of 1 H NMR spectrum, in which the methylene proton signals associated with the side-chain OH groups are magnified for clarity, measured at 90 °C in tetrachloroethane-d2.

[0111] Figure 4 : iPP-g-PVL after PVL chain degradation 1 H NMR spectrum, measured in tetrachloroethane-d2 at 90°C.

[0112] Figure 5 : isotactic-poly(propylene-co-undecyl alcohol) precursor and iPP-g-PVL copolymer (iPP 53mol% -g-PVL 47mol% )’s SEC tracking.

[0113] Figure 6: iPP-g-PVL copolymer (iPP 53mol% -g-PVL 47mol% ) AFM of cross sections a) and b) before degradation and c) and d) after degradation.

[0114] Figure 7: a) iPP-g-PVL copolymer (iPP) before (solid line) and after (dashed line) PVL degradation 53mol% -g-PVL 47mol% ) and b) iPP-g-PCL copolymer (iPP before (solid line) and after (dashed line) PCL degradation 53mol% -g-PCL 47mol% )'s stress-strain curve of the tensile test.

[0115] Figure 8: iPP-g-PVL copolymer (iPP 53mol% -g-PVL 47mol% ), b) iPP-g-PCL copolymer after degradation (iPP 53mol% -g-PCL 47mol% )FE-SEM of the porous membrane formed.

[0116] Figure 9: a) Nitrogen adsorption measurements on porous membranes measured at T = 77 K, showing the adsorption (solid squares) and desorption (empty squares) isotherms; b) Pore size distribution of porous membranes after PVL or PCL degradation calculated according to nitrogen adsorption (solid squares) and desorption (empty squares) isotherms.

[0117] Fig.10 : Filter device.

[0118] Fig.11 : DLS of silica nanoparticle dispersion before and after filtration.

[0119] Figure 12: 3D simulation display of the embodiment: 12a, 12e and 12f are comparative examples, which are not within the scope of the present invention; 12b, 12c and 12d are embodiments of the present invention.

[0120] References:

[0121] [1] (a) Baker, RWMembrane Technology and Applications, Wiley, West Sussex, 2004. (b) Nunes, SP; Car, A. Ind. Eng. Chem. 2013, 52, 993–1003.

[0122] [2] (a) Bierenbaum, HS; Isaacson, RB; Druin, ML; Plovan, SGInd.

[0123] [3](a)Fleisher,RL;Alter,HW;Furman,SC;Price,PB;Walker,RMScience 1972,172,225–263.(b)Awasthi,K.;Kulshrestha,V.;Acharya,NK;Singh,M.;Vijay,YKEur.Polym.J.2006,42,883–887.

[0124] [4](a)Ichikawa,T.Takahara,K.Shimoda,K.Seita,Y.Emi,M.US 4,708,800;Terumo Kabushiki Kaisha,1987.(b)Chau,CC,Im,J.-h.US 4,874,568;The DOWChemical Company,1989.(c)Lopatin,G.Yen,LY,Rogers,RRUS 4,874,567;MilliporeCorporation,1989.

[0125] [5]For example see:(a)Zhang,Y.Sargent,JL;Boudouris,BW;Phillip,WAJAppl.Polym.Sci.

[0126] [6](a)Smith,DRMeier,DJPolymer 1992,33,3777–3782.(b)Ndoni,S.Vigild,ME;Berg,RHJAm.Chem.Soc.2003,125,13366–13367. c)Zalusky,AS;Olayo-Valles,R.Wolf,JH;Hillmyer,MAJAm.Chem.Soc.2002,124,12761–12773.

[0127] [7](a) Ring, J.O.; Thomann, R.; Müllhaupt, R.; Raquez, J.-M.; Degée, P.; Dubois, P. Macromol. Chem. Phys. 2007, 208, 896–302. (b) Pitet, L.M.; Amendt, M.A.; Hillmyer, M.A. J. Am. Chem. Soc. 2010, 132, 8230–8231. (c) Hillmyer, M.; Pitet, L.; Amendt, M. (University of Minnesota) US 9,051,421 B2, 2015. (d) Kato, T.; Hillmyer, M.A. ACS Appl. Mater. Interfaces 2013, 5, 291-300. (e) Pillai, S.K.T.; Kretschmer, W.P.; Trebbin, M.; S.; Kempe, R. Chem. Eur. J. 2012, 18, 13974–13978.

[0128] [8] The only example reported so far consist of nonporous poly(vinylidene fluoride)-graft-poly(meth)acrylate graft copolymers. For example see: Hester, J.F.; Banerjee, P.; Won, Y.-Y.; Akthakul, A.; Acar, M.H.; Mayes, A.M. Macromolecules 2002, 35, 7652–7661.

[0129] [9] Wolf, J.H.; Hillmyer, M.A. Langmuir 2003, 19, 6553–6560.

[0130]

[10] Brunauer, S.; Deming, L.S.; Deming, W.E.; Teller, E. J. Am. Chem. Soc. 1940, 62, 1723–1732.

[0131]

[11] Barrett, E.P.; Joyner, L.G.; Halenda, P.P. J. Am. Chem. Soc. 1951, 73, 373–380.

[0132] Experimental Section

[0133] Measurement method

[0134] Material:

[0135] δ-Valerolactone (VL; 98%, TCI) ε-Caprolactone (CL; 97%, Sigma-Aldrich) was dried over CaH2 (95%, Sigma-Aldrich) and distilled under reduced pressure. Ether was used as received. Toluene (anhydrous, Sigma-Aldrich) was purified using an MBraun-SPS-800 purification column system and stored in a 1% ethanol solution under an inert atmosphere. 10-Undecen-1-ol was purchased from Sigma-Aldrich and was heated under an inert atmosphere with Molecular sieve drying. Methylaluminoxane (MAO) (30 wt % in toluene) was purchased from Chemtura. Diethylzinc (DEZ) (1.0 M in hexane), triisobutylaluminum (TiBA) (1.0 M in hexane), and racemic-Me2Si(2-Me-4-Ph-Ind)2ZrCl2 were all purchased from MCAT GmbH, Konstanz, Germany. Isotactic polypropylene (i-PP) (SABIC-PP520P, MFR=10.5 g / 10 min (230°C / 2.16 kg)), 2-ethylhexanoate tin (II) (Sn(Oct)2) (92-100%, Sigma-Aldrich), n-butoxide titanium (IV) (Ti(OBu)4, Sigma Aldrich), and Irganox 1010 (antioxidant, BASF) were all used as received.

[0136] Synthesis of isotactic poly(propylene-co-10-undecen-1-ol) (iPP-OH).

[0137] The copolymerization reaction was carried out in a stainless steel Büchi reactor (300 mL). Before polymerization, the reactor was dried in vacuum and flushed with nitrogen. Under a nitrogen atmosphere, toluene (100 mL) was introduced into the reactor, followed by TiBA (1.0 M in hexane, 5 mL) and a functionalized comonomer (10-undecene-1-ol; 1 mL, 2.5 mmol). The resulting solution was stirred for 15-20 min. MAO (30 wt % in toluene, 2.0 mL) was subsequently introduced into the reactor under a nitrogen atmosphere. The solution was saturated with propylene (5 bar). In a glove box, a raw material solution of racemic-Me2Si(2-Me-4-Ph-Ind)2ZrCl2 (5 mg, 8 μmol) in toluene (10 mL) was prepared under a nitrogen atmosphere, and the catalyst solution (5 mL) was transferred to the reactor. The propylene pressure was maintained constant for 30 min. At the end of the reaction, the propylene feed was stopped and the residual propylene was released from the reactor. The resulting mixture was quenched in acidified methanol (300 mL, 2.5 wt% concentrated HCl), filtered and washed with deionized water. The resulting powder was dried in a vacuum oven at 60°C under reduced pressure overnight.

[0138] Typical polymerization process of PP-graft-PCL via catalytic ring-opening polymerization.

[0139] iPP-OH (4 g, M n =27.8 kDa, ) was placed in a round-bottom flask with a magnetic stirrer and dried by Dean-Stark distillation in toluene (100 mL) for 24 h. The solution was then cooled to 100 °C and the catalyst Sn(Oct)2 (180 mg) and ε-caprolactone (10.3 g, 89.9 mmol) were added. The reaction was carried out under an inert atmosphere for 24 h. By taking aliquots of samples at set time intervals, 1 The copolymerization process was followed by H NMR spectroscopy. The synthesized copolymer was isolated by precipitation in diethyl ether and dried in a vacuum oven at 40 °C for 24 h.

[0140] Typical polymerization process of PP-graft-PVL via catalytic ring-opening polymerization.

[0141] iPP-OH (4 g, M n =27.8 kDa, ) was placed in a round-bottom flask with a magnetic stirrer and dried by Dean-Stark distillation in toluene (100 mL) for 24 h. The solution was then cooled to 100 °C and the catalyst Sn(Oct)2 (180 mg) and δ-valerolactone (10.0 g, 100 mmol) were added. The reaction was carried out under an inert atmosphere for 24 h. By taking aliquots at set time intervals, 1The copolymerization process was followed by H NMR spectroscopy. The synthesized copolymer was isolated by precipitation in diethyl ether and dried in a vacuum oven at 40 °C for 24 h.

[0142] Typical process for the synthesis of PP-graft-PCL copolymers via transesterification.

[0143] iPP-OH (4 g, M n =27.8 kDa, ) and PCL (6 g, M n =42.0 kDa, ) was premixed with the antioxidant Irganox 1010 (2500 ppm) for 5 minutes and fed into a co-rotating twin-screw micro-extruder at 190° C. with a screw rotation speed of 100 rpm. After this, tin(II) 2-ethylhexanoate (0.09 g, 0.22 mmol) was added as a catalyst and the mixture was stirred for a further 5 minutes. The extruder chamber was then cooled and vented.

[0144] Compression molding experiment All films were prepared by compression molding on a LabEcon 600 high temperature press (Fontijne Presses, the Netherlands) using PP ISO equipment. The copolymers were introduced into a Teflon mold to prepare samples with a thickness of 0.18 mm. The compression molding procedure consisted of the following steps: heating to 200 °C at 5 bar for 5 min and cooling to room temperature at 5 bar for 10 min.

[0145] Film formation:

[0146] Degradation of the polyester sequence of the copolymer was performed by immersing the copolymer film in a 0.5 M NaOH solution in a mixture of water and methanol (60:40). The solution was kept at 70 °C for 3 days, and then the porous membrane was washed with slightly acidic MeOH (aq), then with pure MeOH, and dried under vacuum for 24 h.

[0147] Filters:

[0148] The volume flux of the membrane was measured by the following procedure: The porous membrane was clamped on a glass filtration device, then vacuum (20 mbar) was applied and water was added on top of the filtration device.

[0149] Apply formula 1 to calculate the volume flow rate, which is equal to 75L.m -2 .h -1 .

[0150]

[0151] Formula 1: Volume flow rate

[0152] Among them J V is the volume flow rate, V is the volume (L), A is the membrane area (m 2 ) and t is the time (h).

[0153] Then, a 3% (w / v) dispersion of silica nanoparticles in ethanol (particle size less than 100 nm) was used for filtration experiments. The dispersion was filtered using the same filtration device, and DLS experiments were performed on the solution before and after filtration. After filtration, no signal was detected by DLS, proving that the porous membrane filtered out the silica nanoparticles.

[0154] Characterization

[0155] 1 H NMR: The measurements were carried out at 90° C. using deuterated tetrachloroethane (TCE-d2) as solvent and recorded on a Bruker spectrometer operating at a frequency of 300 MHz in 5 mm tubes. The chemical shifts in ppm to TCE-d2 were determined by reference to the residual solvent signal.

[0156] HT-SEC: M n 、M w and polydispersity index (PDI, ) Determination by Size Exclusion Chromatography: SEC measurements were made at 150°C in an Agilent GC oven model 7890 equipped with an autosampler and an integrated detector IR4. 1,2-Dichlorobenzene (o-DCB) was used as the eluent at a flow rate of 1 mL / min. Calculations Software GPC Processing SEC data.

[0157] DSC: Melting temperatures (T) were measured by differential scanning calorimetry (DSC) using a DSC Q100 from TA Instruments. m ) temperature and crystallization (T c ) temperature and transition enthalpy. At 10℃·min -1 The measurements were performed from -60°C to 230°C at a heating and cooling rate of 1.5 %. The transition was inferred from the second heating and cooling curve.

[0158] Field emission scanning electron microscopy (FE-SEM) imaging.The cross-sectional morphology of the degraded self-assembled copolymer films was characterized by FE-SEM imaging (JEOL JSM 7800-F) using an LED detector at an operating voltage of 5 kV. In order to obtain sufficient contrast of the membrane nanopore morphology and avoid damaging the membrane cross section, the samples used for FE-SEM imaging were first immersed in liquid nitrogen to fracture them and then sputtered with platinum / palladium (Pt / Pd).

[0159] Atomic force microscopy (AFM) analysis.

[0160] Sample preparation: For spin-coated self-assembled copolymer films, AFM imaging was performed directly on the film surface under ambient conditions without further sample processing. To image the film cross-section before and after degradation, the specimen was cut into appropriate samples and then cryosectioned at -120°C using a microtome (LEICA EM UC7). The sample was sectioned using a diamond knife (Diatome) mounted on a stainless steel holder. This cross-sectional fragment was used directly for AFM measurements without further processing.

[0161] AFM analysis: On the Dimension FastScan AFM system from Bruker, the AFM tip (Model TESPA-V2, k: 42N / m, f: 320kHz) of the tapping mode was used to implement AFM imaging. Software NanoscopeAnalysis 1.5 from Bruker was used as a computer interface for operating and analyzing AFM measurements. All AFM measurements were implemented under ambient conditions. Height and phase maps were recorded simultaneously at a scan rate of 1 Hz and a resolution of 512 x 512 pixels. Before AFM measurement, the imaging region of interest was first selected using the optical imaging integrated in the AFM device.

[0162] Pore ​​size analysis: Nitrogen adsorption–desorption isotherms were measured at −196 °C using a Micromeritics ASAP 2420 analyzer. Prior to the measurements, the samples were degassed overnight at 30 °C under high vacuum (133 Pa). The specific surface area of ​​the membranes was calculated using the Brunauer–Emmet–Teller method

[10] , while the pore size distribution was determined using the Barret–Joyner–Halenda model

[11] .

[0163] Dynamic Mechanical Thermal Analysis : DMTA was performed using a TA Instruments Q800 DMA measurement. The samples were tested by a strain-controlled temperature ramp with a frequency of 1 Hz. The temperature profile was from -100°C to the melting point of the polyolefin segment with a ramp rate of 3°C / min. The glass transition temperature was calculated as the peak value of the tangent increment signal.

[0164] Mechanical properties analysis: The mechanical properties were characterized by repeating the tensile test three times using a micro tensile tester (Linkam, TST 350). The two ends of the tensile specimen (length: 30 mm, width: 2 mm, thickness: 0.18 mm) were clamped by jaws with a spacing of 15 mm. A load cell with a capacity of 200 N was used to measure the applied force. The tensile test was performed at room temperature at a constant speed of 50 μm / s.

[0165] Table 1 Copolymer composition (volume and molar fraction) (with 1 H NMR measurement)

[0166]

[0167] a For PVL, it is the valerolactone unit, while for PCL, it is the caprolactone unit.

[0168] Table 2 is composed of 1 Copolymer properties characterized by H NMR and SEC

[0169]

[0170] a Molar mass (kDa) and polydispersity index (D M ) were measured at 150°C in o-DCB with HT-SEC (applying PS standard and Mark-Houwink parameters).

[0171] b The amount of side chain OH groups on each chain is given by 1 H NMR confirmed.

[0172] c The molar mass of PVL is 1 H NMR measurements.

[0173] Table 3 Thermal characteristics

[0174]

[0175] a T measured by DSC c and T m .

[0176] Table 4 Mechanical properties

[0177] <![CDATA[Young's modulus (MPa) a > <![CDATA[Tensile toughness (J / m 3 ) a > <![CDATA[OH / Chain b > <![CDATA[PP 53mol% -g-PCL 47mol% ]]> 660 35.1 6 <![CDATA[PP 53mol% -g-PVL 47mol% ]]> 415 85.3 6 <![CDATA[PP 56mol% -g-PVL 44mol% ]]> 740 21.3 6 <![CDATA[PP after degradation 53mol% -g-PCL 47mol% > 225 5.6 6 <![CDATA[PP after degradation 53mol% -g-PVL 47mol% > 145 1.9 6 <![CDATA[PP after degradation 56mol% -g-PVL 44mol% > 186 2.6 6 <![CDATA[PP 52mol% -g-PCL 48mol% ]]> 733 <![CDATA[6930 b ]]> 3 <![CDATA[PP 52mol% -g-PVL 48mol% ]]> 780 4.7 3 <![CDATA[PP 63mol% -g-PVL 37mol% ]]> 787 32.1 3 <![CDATA[PP 66mol% -g-PVL 34mol% ]]> 670 11.71 3 <![CDATA[PP after degradation 52mol% -g-PCL 48mol% > 120 0.6 3 <![CDATA[PP after degradation 52mol% -g-PVL 48mol% > 106 0.7 3 <![CDATA[PP after degradation 63mol% -g-PVL 37mol% > 115 0.4 3 <![CDATA[PP after degradation 66mol%- g-PVL 34mol% > 180 1.43 3

[0178] a Young's modulus and tensile toughness were determined by tensile tests.

[0179] b A very ductile material that can be deformed to the maximum tensile strength (500%) without breaking.

[0180] Table 5 Porosity characteristics

[0181]

[0182] a Pore ​​size distribution measured by the Barret–Joyner–Halenda model.

[0183] b Surface area determined by the Brunauer–Emmet–Teller method.

Claims

1. A film comprising a random graft copolymer having a polypropylene (PP) backbone and 3 to 8 polyester segments covalently bonded to the PP backbone, wherein the random graft copolymer is composed of 1 H NMR measurements of PP and polyester segments with 3-8 -OH functional groups per polymer chain randomly distributed on the side chains of the polymer backbone, obtained by coupling the polyester segments to the -OH functional groups of PP, The number average molecular weight M of the PP skeleton is n 10-100 kDa, The M of each polyester segment n 5-25 kDa, The amount of PP is 45-80 mol%. The amount of polyester segments is 55-20 mol%. The thickness of the film is 0.01-10 mm. wherein the PP and polyester regions form a helical bicontinuous morphology, wherein the mol % is calculated relative to the total number of moles of monomer units present in the copolymer, Wherein, after the segment sacrificial process, the polyester segments self-arrange in regions suitable for forming porous channels through the film.

2. The film of claim 1, wherein the PP backbone is prepared from a PP-homopolymer or a copolymer of propylene and ethylene, wherein the amount of ethylene is less than 5 wt%, and wherein the PP is isotactic or syndiotactic.

3. The film of claim 1 or 2, wherein the PP in the copolymer backbone has a number average molecular weight Mn of 20-100 kDa and a melting temperature of at least 120°C.

4. The film of claim 3, wherein the melting temperature of the PP in the copolymer backbone is 140-160°C.

5. The film of claim 1 or 2, wherein the Young's modulus of the film is 300-1500 MPa, and the toughness of the film is 1-150 J / m 3 .

6. The film of claim 5, wherein the Young's modulus of the film is 400-1000 MPa, and the toughness of the film is 4-100 J / m 3 .

7. The film of claim 1 or 2, wherein the polyester segment comprises monomer units derived from caprolactone and / or valerolactone.

8. The film of claim 1 or 2, wherein the amount of PP is 50-75 mol% and the amount of polyester is 50-25 mol%.

9. A nanoporous membrane based on a random graft copolymer having a polypropylene (PP) backbone and 3 to 8 polyester segments covalently bonded to the PP backbone, wherein the random graft copolymer is composed of 1 H NMR determination of PP and polyester segments with 3-8 -OH functional groups per polymer chain randomly distributed on the side chains of the polymer backbone, obtained by coupling the polyester segments to the -OH functional groups of PP, the nanoporous membrane comprising at least 90 wt% of PP, and wherein the Mn of the PP in the membrane is 10-100 kDa.

10. The film of claim 9, wherein the M of the PP in the film is n The molecular weight of the PP is 20-100 kDa, and the PP is isotactic or syndiotactic.

11. The film of claim 9 or 10, wherein the film has a thickness of 0.01 to 10 mm, The membrane has pores with a size of 10-50 nm as measured by N2-desorption according to the Barret-Joyner-Halenda model and a pore size of 50-200 nm as determined by the Brunauer-Emmet-Teller method. 2 / g of BET surface area.

12. The film of claim 9 or 10, wherein the film has a melting temperature T measured by DSC. m It is 120-160℃.

13. The film of claim 12, wherein the film has a melting temperature T measured by DSC. m It is 140-158℃.

14. The film of claim 9 or 10, wherein the Young's modulus of the film is 50-400 MPa, and the toughness of the film is 0.1-15 J / m 3 .

15. The film of claim 14, wherein the Young's modulus of the film is 100-300 MPa, and the toughness of the film is 0.5-10 J / m 3 .

16. Use of the film according to any one of claims 1 to 8 for the preparation of a membrane suitable for use as a water filter or battery separator.

17. A water filter system comprising a nanoporous membrane as defined in any one of claims 9 to 15.

18. A battery comprising a nanoporous membrane as defined in any one of claims 9 to 15.

19. A PP film unit, which is a multilayer film or a plurality of films, wherein a layer of the multilayer film or the plurality of films comprises: The nanoporous membrane according to any one of claims 9 to 15, and Microporous PP films and / or PP nonwovens.

Citation Information

Patent Citations

  • Polar group-containing olefin copolymer, process for preparing the same, thermoplastic resin composition contaning the copolymer, and uses thereof

    EP1186619A2

  • Interrupt Scheme for Bus Controller

    US20070208896A1

  • Hollow fiber membrane and method for manufacture thereof

    US4708800A

  • Microporous membranes from polypropylene

    US4874567A

  • Process of making a porous membrane

    US4874568A